3
$\begingroup$

I've given this Hamiltonian with one degree of freedom: $$ H(x,p)=\frac{p^2}{2}+\frac{\omega_0^2x^2}{2}+\lambda\left(\frac{p^2}{2}+\frac{\omega_{0}^2x^2}{2}\right)^2 $$ I need to find the general solution for the motion of this particle $(x(t),p(t))$. It's required to solve the equations of motion, not only find them. I showed that $f = p^2+\omega_{0}^2x^2 $ is time independent by computing: $$\{f,H\}=0$$ But I'm having a hard getting the final solution. I tried doing: $$ 2p\dot{p}+2\omega_{0}^2x\dot{x}=\dot{f}=0 $$ $$ \dot{p}=-\frac{\omega_{0}^2x\dot{x}}{p} $$ And then: $$ \newcommand{\pder}[2][]{\frac{\partial#1}{\partial#2}} \dot{p}=-\pder[H]{x} $$ Same for $\dot{x}$. Yet, I don't obtain nicer differential equations and I don't think it's the right approach. Could someone give me a hint?

$\endgroup$
  • $\begingroup$ Hi. Do you need to find the equations of motion or solve the equations of motion? Thanks. $\endgroup$ – Constantine Black Nov 22 '16 at 20:34
  • $\begingroup$ I need to solve them $\endgroup$ – user3903647 Nov 22 '16 at 20:34
2
$\begingroup$

I want simplification, so I'll take $\omega_0 = 1$. You can rescale $x$ and always get this kind of simplification, if $\omega_0$ is a constant. The Hamiltonian then becomes

$$H(x,p) = \frac{p^2}{2} + \frac{q^2}{2} + \lambda \left( \frac{p^2}{2} + \frac{q^2}{2} \right)^2 \, .$$

Hamilton's equations are given by

\begin{align} \begin{cases} \dot{q} &= p + 2 \lambda p \left( \frac{p^2}{2} + \frac{q^2}{2} \right) \\ \dot{p} &= -q - 2 \lambda q \left( \frac{p^2}{2} + \frac{q^2}{2} \right) \end{cases} \quad \Rightarrow \quad \begin{cases} \dot{q} &= p \left[1 + 2 \lambda \left( \frac{p^2}{2} + \frac{q^2}{2} \right) \right] \\ \dot{p} &= -q \left[1 + 2 \lambda \left( \frac{p^2}{2} + \frac{q^2}{2} \right) \right] \end{cases} \, . \end{align}

Assuming $q, \dot{p} \neq 0$, divide one equation by the other to get

$$ \frac{ \left( \frac{dq}{dt} \right)}{ \left(\frac{dp}{dt} \right)} = \frac{p \left[1 + 2 \lambda \left( \frac{p^2}{2} + \frac{q^2}{2} \right) \right]}{-q \left[1 + 2 \lambda \left( \frac{p^2}{2} + \frac{q^2}{2} \right) \right]} = -\frac{p}{q} \, .$$

The solution will, therefore, be the same as for the SHO, with the exception that the new frequency will increase as the orbit gets farther away from the origin.

As I believe this is homework, I'll give no further details. The problem is basically solved.

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.